Loss of Endothelial Cytochrome P450 Reductase Induces Vascular Dysfunction in Mice. Issue 6 (31st March 2022) - Malacarne, Pedro Felipe; Ratiu, Corina; Gajos-Draus, Anna; Müller, Niklas; Lopez, Melina; Pflüger-Müller, Beatrice; Ding, Xinxin; Warwick, Timothy; Oo, James; Siragusa, Mauro; Angioni, Carlo; Günther, Stefan; et al.
Abstract : Background: POR (cytochrome P450 reductase) provides electrons for the catalytic activity of the CYP (cytochrome P450) monooxygenases. CYPs are dual-function enzymes as they generate protective vasoactive mediators derived from polyunsaturated fatty acids but also reactive oxygen species. It is not known in which conditions the endothelial POR/CYP system is beneficial versus deleterious. Here, the activity of all CYP enzymes was eliminated in the vascular endothelium to examine its impact on vascular function. Methods: An endothelial-specific, tamoxifen-inducible POR knockout mouse (ecPOR − /− ) was generated. Vascular function was studied by organ chamber experiments. eNOS (endothelial nitric oxide synthase) activity was accessed by heavy arginine/citrulline LC-MS/MS detection and phosphorylation of serine1177 in aortic rings. CYP-derived epoxyeicosatrienoic acids and prostanoids were measured by LC-MS/MS. Gene expression of aorta and endothelial cells was profiled by RNA sequencing. Blood pressure was measured by telemetry. Results: Acetylcholine-induced endothelium-dependent relaxation was attenuated in isolated vessels of ecPOR −/− as compared with control mice. Additionally, ecPOR −/− mice had attenuated eNOS activity and eNOS/AKT phosphorylation. POR deletion reduced endothelial stores of CYP-derived epoxyeicosatrienoic acids but increased vascular prostanoids. This phenomenon was paralleled by the induction of genes implicated in eicosanoid generation. In response to Ang II (angiotensin II) infusion, blood pressure increased significantly more in ecPOR − /− mice. Importantly, the cyclooxygenase inhibitor Naproxen selectively lowered the Ang II–induced hypertension in ecPOR − /− mice. Conclusions: POR expression in endothelial cells maintains eNOS activity and its loss results in an overactivation of the vasoconstrictor prostanoid system. Through these mechanisms, loss of endothelial POR induces vascular dysfunction and hypertension.